Radiation refrigeration-hydrogel power generation composite material and preparation method and application thereof
By designing a radiation cooling-hydrogel power generation composite material, and utilizing the porous conductive network of PVDF/PPy porous membrane and chitosan/acrylic hydrogel layer, the problems of low heat dissipation efficiency and poor flexibility of traditional radiation cooling materials are solved, achieving a highly efficient energy closed loop, which is suitable for self-powered cooling systems and smart wearable devices.
Patent Information
- Application Number
- CN202511458841.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-13
- Publication Date
- 2025-12-09
AI Technical Summary
Traditional radiative cooling materials have low porosity and lack conductive fillers, resulting in insufficient heat dissipation efficiency. They also have poor flexibility, and a single wet gas generator cannot be integrated with the refrigeration system, leading to low energy efficiency.
A radiation cooling-hydrogel power generation composite material is designed, comprising a PVDF/PPy porous membrane and a chitosan/acrylic hydrogel layer. The PVDF/PPy porous membrane is prepared by electrospinning, and combined with a PPy coating and nano-carbon black to form a porous conductive network, thereby realizing the vertical coupling of radiation cooling and moisture power generation.
It improves radiative heat dissipation efficiency, enhances material flexibility and energy efficiency, and forms an energy closed loop of "passive heat dissipation - active power generation," making it suitable for self-powered cooling systems, energy-saving buildings, and smart wearable devices.
Smart Images

Figure CN121084010A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of new energy materials and intelligent temperature control materials, and particularly relates to a radiation refrigeration-hydrogel power generation composite material and a preparation method and application thereof. BACKGROUND
[0002] Driven by global energy crisis, the application of clean energy in the field of radiation refrigeration has strategic significance. Passive thermal management technology and environmental energy collection technology have become the core direction of sustainable development. As a passive cooling technology, radiation refrigeration realizes energy-free cooling efficiency through high emissivity of materials in the mid-infrared band; the wetness power generation technology uses ion migration of hydrogel and other materials to adsorb environmental humidity to generate electric energy, providing micro energy for sensors and wearable devices.
[0003] Traditional radiation refrigeration materials have certain infrared emissivity, but have low porosity and lack of conductive fillers, resulting in insufficient radiation cooling efficiency; at the same time, single metal oxide coating has poor flexibility and weak bonding force, which is difficult to be used in flexible devices; and single wetness power generator cannot be integrated with the refrigeration system, resulting in low energy efficiency and obvious structural defects. SUMMARY
[0004] In view of the technical problems in the background art, the present application provides a radiation refrigeration-hydrogel power generation composite material and a preparation method and application thereof, aiming to solve the technical problems of insufficient radiation cooling efficiency, poor flexibility, inability to integrate with the refrigeration system, and low energy efficiency.
[0005] In a first aspect, the present application provides a radiation refrigeration-hydrogel power generation composite material, comprising a radiation refrigeration layer and a hydrogel power generation layer, the radiation refrigeration layer comprising a PVDF / PPy porous film, and the surface of the PVDF / PPy porous film being provided with a PPy coating layer; and the hydrogel power generation layer comprising a chitosan / acrylic acid hydrogel, lithium chloride and nano carbon black.
[0006] In a second aspect, the present application provides a preparation method of the radiation refrigeration-hydrogel power generation composite material, comprising the following steps: S1, adding PVDF, methylpyrrolidone, PPy, polyvinylpyrrolidone and TiO2 into dimethylformamide, stirring and dissolving to obtain a dispersion liquid, and electrospinning the dispersion liquid as raw material to obtain a PVDF / PPy porous film; S2, dispersing PPy in DMF to obtain a PPy dispersion liquid, immersing the PVDF / PPy porous film in the PPy dispersion liquid, and ultrasonic treatment and drying to obtain the radiation refrigeration layer; S3, dispersing acrylic acid, chitosan, lithium chloride and nano carbon black in deionized water to obtain a mixed solution; S4, add initiator and crosslinking agent to the mixed solution, stir and react to obtain a hydrogel power generation layer; S5, cover the radiation refrigeration layer on the surface of the hydrogel, freeze for 4-6h, and then vacuum dry to obtain a radiation refrigeration-hydrogel power generation composite material.
[0007] In a third aspect, the embodiments of the present application provide an application of the radiation refrigeration-hydrogel power generation composite material in a self-powered cooling system, an energy-saving building coating or a portable cold chain packaging.
[0008] Compared with the prior art, the beneficial effects of the present application include: 1. The present application provides a radiation refrigeration-hydrogel power generation composite material, which comprises an upper radiation refrigeration layer and a lower hydrogel power generation layer. The PVDF (polytetrafluoroethylene) in the upper radiation refrigeration layer has a natural high infrared emissivity in the atmospheric window, has a radiation refrigeration effect, is prepared into a PVDF / PPy porous membrane by electrospinning, the porous structure can increase the heat dissipation area, and after embedding PPy (polypyrrole) and titanium dioxide, the titanium dioxide enhances sunlight reflection and improves the radiation refrigeration efficiency.
[0009] Through the upper PVDF hydrophobicity and the lower hydrogel power generation layer contacting air and absorbing moisture, a wet-dry gradient is formed, and the environmental humidity is converted into electric energy. LiCl and nano carbon black in the hydrogel power generation layer can improve the ion concentration and mobility. The PVDF radiation refrigeration layer creates a moisture-retaining ideal power generation environment for the hydrogel power generation layer through temperature regulation. The stable ion flow of the hydrogel power generation layer reduces the heat dissipation burden, forms an energy closed loop of "passive heat dissipation-active power generation", and enhances the system stability.
[0010] 2. The present application vertically couples the radiation refrigeration-humidity power generation through the design of the double-layer heterogeneous structure and the construction of the porous conductive network, realizes the energy closed loop of "passive heat dissipation-active power generation", provides core support for constructing the "zero-carbon refrigeration" technical system, and provides a new technical path in the fields of building energy saving, cold chain logistics, intelligent wearable devices, etc., reduces the consumption of fossil energy, realizes continuous energy supply through environmental energy collection, and meets the global energy transformation and sustainable development needs.
[0011] 3. The raw materials of the present application are mainly conventional polymers such as PVDF, acrylic acid and chitosan, which are low in cost. The preparation process is controllable and suitable for large-scale production. Compared with the same type of high-cost and low-yield products, the commercial application potential of the present application is greater.
[0012] The above description is only a summary of the technical solutions of the present application. In order to more clearly understand the technical means of the present application, the specific embodiments of the present application can be implemented in accordance with the content of the description, and in order to make the above and other purposes, characteristics and advantages of the present application more obvious and easy to understand, the following specific embodiments of the present application are described. Attached Figure Description
[0013] To more clearly illustrate the technical solution of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0014] Figure 1 This is a SEM image of the surface radiation cooling film of the asymmetric structure in Embodiment 1 of the present invention.
[0015] Figure 2 The figures show the cyclic test results of the asymmetric hydrogels of Examples 1-3 of the present invention at the same temperature.
[0016] Figure 3 The temperature curves of the asymmetric hydrogels in Examples 1-3 of this invention were measured under the same humidity.
[0017] Figure 4 The results are the static water contact angle test results of the asymmetric structure surface radiation cooling film of Embodiment 1 of the present invention.
[0018] Figure 5 This is a vt graph of the asymmetric hydrogel of Example 1 of the present invention, measured at the same humidity and temperature.
[0019] Figure 6 The vt plot of the asymmetric structure hydrogel of Comparative Example 1 of this invention was measured at the same humidity and temperature.
[0020] Figure 7 This is a tensile property diagram of the asymmetric hydrogel of Example 1 of the present invention. Detailed Implementation
[0021] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0023] Traditional radiation cooling materials have certain infrared emissivity, but low porosity and lack of conductive fillers, resulting in insufficient radiation heat dissipation efficiency; at the same time, single metal oxide coating is poor in flexibility and weak in bonding force, and is difficult to be used in flexible devices; and single humidity generator cannot be integrated with a refrigeration system, resulting in low energy efficiency and obvious structural defects.
[0024] In order to solve the technical problems of insufficient radiation heat dissipation efficiency, poor flexibility, inability to integrate with a refrigeration system and low energy efficiency, the present application provides a radiation cooling-hydrogel power generation composite material and a preparation method and application thereof, which vertically couples radiation cooling and humidity power generation through the design of a double-layer heterogeneous structure and the construction of a porous conductive network, and realizes an energy closed loop of "passive heat dissipation-active power generation".
[0025] In a first aspect, the embodiments of the present application provide a radiation cooling-hydrogel power generation composite material, which comprises a radiation cooling layer and a hydrogel power generation layer, the radiation cooling layer comprises a PVDF / PPy porous film, and the surface of the PVDF / PPy porous film is provided with a PPy coating layer; and the hydrogel power generation layer comprises a chitosan / acrylic acid hydrogel, lithium chloride and nano carbon black.
[0026] In the technical scheme of the embodiments of the present application, the PVDF (polytetrafluoroethylene) in the upper radiation cooling layer itself has a natural high infrared emissivity in the atmospheric window, has a radiation cooling effect, is prepared into a PVDF / PPy porous film through electrospinning, the porous structure can increase the heat dissipation area, after embedding PPy (polypyrrole) and titanium dioxide, the PPy serves as a flexible conductive polymer to improve the mechanical flexibility of the PVDF film, the PPy is uniformly dispersed in the PVDF matrix to form a continuous conductive path and a porous structure inside the film; and the titanium dioxide enhances sunlight reflection and improves the radiation cooling efficiency.
[0027] Through the upper PVDF hydrophobicity and the lower hydrogel power generation layer contacting air to absorb moisture, a wet-dry gradient is formed to convert environmental humidity into electrical energy, and the LiCl and nano carbon black in the hydrogel power generation layer can improve the ion concentration and mobility; the PVDF radiation cooling layer creates a moisture-retaining ideal power generation environment for the hydrogel power generation layer through temperature regulation, and the stable ion flow of the hydrogel power generation layer reduces the heat dissipation burden, forming an energy closed loop of "passive heat dissipation-active power generation" to enhance the system stability.
[0028] In a second aspect, the embodiments of the present application provide a preparation method of a radiation cooling-hydrogel power generation composite material, which comprises the following steps: S1, PVDF, methylpyrrolidone, PPy, polyvinylpyrrolidone and TiO2 are added to dimethylformamide, stirred and dissolved to obtain a dispersion liquid, and electrospinning is performed with the dispersion liquid as a raw material to obtain a PVDF / PPy porous membrane; the design of the porous structure can increase the surface area and improve the heat dissipation efficiency; the humidity conduction rate is adjusted to drive ion migration to generate electricity.
[0029] S2, PPy is dispersed in DMF to obtain a PPy dispersion liquid, the PVDF / PPy porous membrane is immersed in the PPy dispersion liquid, and ultrasonic treatment is performed, and after drying, a radiation refrigeration layer is obtained; a PPy coating layer is coated on the PVDF / PPy porous membrane, the PPy coating layer is combined with chitosan in the hydrogel through π-π interaction and hydrogen bonding, and the bonding force between the two layers is enhanced.
[0030] S3, acrylic acid, chitosan, lithium chloride and nano carbon black are dispersed in deionized water to obtain a mixed solution; S4, an initiator and a crosslinking agent are added to the mixed solution, and after stirring and reaction, a hydrogel power generation layer is obtained; S5, the radiation refrigeration layer is covered on the surface of the hydrogel, and after being frozen for 4-6 hours, vacuum drying is performed to obtain a radiation refrigeration-hydrogel power generation composite material.
[0031] In some embodiments, the preparation method of PPy includes the following steps: S11, pyrrole, a surfactant and p-toluenesulfonic acid are dispersed in deionized water to obtain a mixed solution; S12, an aqueous ferric chloride solution is added dropwise into the mixed solution under the condition of 5-7℃, stirring and reaction for 1-2 hours, and after centrifugation, washing and drying, PPy is obtained.
[0032] In some embodiments, the surfactant in step S11 includes at least one of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate.
[0033] In the technical scheme of the embodiments of the present application, the addition of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate surfactants can limit the chain growth direction during pyrrole polymerization to form nano-scale short-chain PPy.
[0034] In some embodiments, the mass concentration of PVDF in the dispersion liquid in step S1 is 10%-15%, and the mass concentration of PPy is 5%-10%.
[0035] In some embodiments, the electrospinning parameters in step S1 are set as follows: spinning voltage 18kV, receiving voltage 6kV, pushing speed 0.13mm / min, receiving distance 15cm, and spinning under the condition of ambient temperature 25±2℃ and relative humidity 40±5%.
[0036] In the technical scheme of the embodiment of the application, the high porosity structure is constructed through electrostatic spinning, and uniform dispersion of each component of the raw material is realized.
[0037] In some embodiments, the porosity of the radiation refrigeration layer in step S2 is 70% to 90%, and the emissivity in the middle infrared waveband of 8 to 13 μm is greater than or equal to 0.9.
[0038] In the technical scheme of the embodiment of the application, the radiation refrigeration layer prepared by the application can realize efficient refrigeration, the PVDF matrix structure is stable and porous, and the cost is low and easy to mass-produce.
[0039] In some embodiments, the mass fraction of the nano-carbon black in the mixed solution in step S3 is 0.5% to 5%. The mass ratio of lithium chloride to chitosan is 1:(2 to 5).
[0040] In the technical scheme of the embodiment of the application, the nano-carbon black and lithium chloride construct a conductive network to improve the power generation performance, and strengthen the moisture absorption and ion migration to improve the power generation efficiency.
[0041] In some embodiments, glycerol is further added to the mixed solution in step S3.
[0042] In the technical scheme of the embodiment of the application, glycerol is beneficial to improving the moisture absorption durability of the hydrogel.
[0043] In some embodiments, the initiator in step S4 is selected from ammonium persulfate, and the crosslinking agent is selected from N,N'-methylenebisacrylamide.
[0044] In a third aspect, the embodiment of the application provides an application of the radiation refrigeration-hydrogel power generation composite material in a self-powered cooling system, an energy-saving building coating, or a portable cold chain packaging.
[0045] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are used only to explain the application, and cannot be understood as a limitation on the application. If the specific technology or condition is not specified in the embodiments, the technology or condition described in the literature in the art or according to the product manual is used. If the reagent or instrument is not specified by the manufacturer, it is a conventional product that can be obtained from the market.
[0046] I. Preparation method Embodiment 1 A preparation method of a radiation refrigeration-hydrogel power generation composite material comprises the following steps: Preparation of the upper PVDF radiation refrigeration layer: (1) Synthesis of polypyrrole: 1. Take 0.67g pyrrole, 0.0729g cetyltrimethylammonium bromide (CTAB), 0.0679g sodium dodecylbenzenesulfonate (SDBS), 1.72g T-p-toluenesulfonic acid (sOH), add deionized water to make 100mL solution, stir until uniform; 2. Slowly add 100mL FeCl3 aqueous solution to the above solution at 5~7℃ low temperature environment, stir while adding, continue to react for 1~2 hours.
[0047] 3. Centrifuge the reaction solution, collect the precipitate, wash with deionized water and dry to obtain polypyrrole.
[0048] (2) Electrospinning: 1. Take 2g PVDF, 1.5g methylpyrrolidone, 0.2g polypyrrole, add 15g dimethylformamide; take 0.16g PVP and dissolve in 1mL dimethylformamide, pour into the above mixture; add 0.3g TiO2 nanoparticles, stir at 60℃ for 40min to ensure uniform dispersion of TiO2; 2. Set appropriate electrospinning parameters: spinning voltage 18kV, receiving voltage 6kV, pushing speed 0.15mm / min, receiving distance 15cm, environmental temperature 25±2℃, relative humidity 40±5%, spin to obtain PVDF / PPy / TiO2 porous membrane.
[0049] (3) Interfacial modification: To enhance the bonding force between the two layers, immerse the PVDF spinning membrane in PPy / DMF solution, the mass concentration of PPy in PPy / DMF solution is 2wt%, ultrasonic treatment for 10~15min, after drying, a thick PPy coating is formed on the surface, and a PVDF radiative cooling layer is obtained.
[0050] (4) Preparation of lower hydrogel power generation layer 1. Dissolve 6g acrylic acid in deionized water, add 0.4g chitosan and 2g lithium chloride, stir until the chitosan is completely dissolved.
[0051] 2. Add 0.2g nano carbon black, ultrasonic dispersion for 30min until uniform; add 0.3g ammonium persulfate and 0.01g N,N'-methylenebisacrylamide, stir uniformly and pour into a preheated to 70℃ mold to form a hydrogel power generation layer with a three-dimensional hydrogel network.
[0052] 3. Put the hydrogel into the refrigerator and freeze for 6h, then put it into the freeze dryer and dry under vacuum conditions for 24 hours to obtain a hydrogel power generation layer with a porous structure.
[0053] (5) Preparation of radiation refrigeration-hydrogel power generation composite material The surface of the hydrogel power generation layer was covered with the PVDF radiation refrigeration layer, and the mixture was placed in a refrigerator and frozen at -20℃ for 6h, and then placed in a freeze dryer and dried under vacuum for 24h to form the radiation refrigeration-hydrogel power generation composite material.
[0054] Example 2 Example 2 differs from Example 1 in that the amount of lithium chloride in the hydrogel power generation layer is different, and the other steps are the same: 6g of acrylic acid was dissolved in 24ml of deionized water, 0.4g of chitosan and 2.5g of lithium chloride were added, and the mixture was stirred until the chitosan was completely dissolved.
[0055] 2g of nano carbon black was added and ultrasonically dispersed until uniformly dispersed; 0.3g of initiator ammonium persulfate and 0.01g of crosslinking agent N,N'-methylenebisacrylamide were added, and the mixture was stirred uniformly and then poured into a mold preheated to 70℃ to form a hydrogel power generation layer with a three-dimensional hydrogel network.
[0056] Example 3 Example 3 differs from Example 1 in that glycerol is also added to the hydrogel power generation layer, and the other steps are the same as in Example 1: 6g of acrylic acid was dissolved in 24ml of deionized water, 0.4g of chitosan, 2g of lithium chloride and 0.5ml of glycerol were added, and the mixture was stirred until the chitosan was completely dissolved.
[0057] 2g of nano carbon black was added and ultrasonically dispersed until uniformly dispersed; 0.3g of initiator ammonium persulfate and 0.01g of crosslinking agent N,N'-methylenebisacrylamide were added, and the mixture was stirred uniformly and then poured into a mold preheated to 70℃ to form a hydrogel power generation layer with a three-dimensional hydrogel network.
[0058] Comparative Example 1 Comparative Example 1 differs from Example 1 in that no nano carbon black is added to the hydrogel conductive layer.
[0059] Comparative Example 2 Comparative Example 2 differs from Example 1 in that no freeze-drying is used in the preparation of the radiation refrigeration-hydrogel power generation composite material in step (5), and the specific steps are as follows: The surface of the hydrogel power generation layer was covered with the PVDF radiation refrigeration layer, and the mixture was dried at 25℃ and 50% humidity for 24h.
[0060] Comparative Example 3 Comparative Example 3 differs from Example 1 in that the chitosan in the hydrogel power generation layer is replaced with an equal amount of polyvinyl alcohol.
[0061] II. Test Methods (1) Surface morphology test: The surface of the radiative cooling film was characterized using a JEOL field emission scanning electron microscope (SEM) for observing the pore structure. The higher the porosity, the stronger the radiative cooling and moisture adsorption capacity.
[0062] (2) Solar reflectance test: The sample was scanned for 2 min using an ultraviolet-visible light spectrophotometer (UV-3600plus) with an integrating sphere, with a step of 2 nm. A reflectance of >90% can reduce solar radiation absorption and achieve efficient cooling in combination with high infrared emissivity.
[0063] (3) Thermocouple test: A K-type thermocouple sensor was placed at the bottom of the asymmetric hydrogel to test the temperature of the structural hydrogel. A two-channel temperature recorder was used to record the real-time temperature. At a distance of 30 cm above the hydrogel, a xenon lamp was used to simulate sunlight, which was vertically irradiated on the surface of the PVDF film with an intensity of 1 kW / m 2 To shield the influence of thermal convection, a layer of polyethylene film was placed above the hydrogel. The relative humidity during temperature measurement was 56-62%.
[0064] (4) Water static contact angle test: The test area was fixed on the test table with double-sided tape, and 5 μL of deionized water was slowly added to the sample surface 1-2 mm above. Within 10-30 s after dropping, the droplet shape was photographed by the instrument camera, and the contact angle was measured. The same area was tested 3-5 times at different positions, and the average value was taken. (Contact angle >90° is hydrophobic) (5) Voltage change test: Measured by a chemical workstation, the copper sheet was tightly attached to the upper and lower surfaces, and the positive and negative electrodes were connected to the upper and lower copper sheets, respectively. After 1 min, the voltage was recorded after it stabilized. The voltage measurement environment was 27-40°C, and the relative humidity was 56-75%.
[0065] (6) Mechanical property test: A universal testing machine was used to test the mechanical properties of the sample at room temperature and a relative humidity of 75%, with a tensile rate of 50 mm / min and a clamping distance of 2 cm.
[0066] III. Analysis of test results of various embodiments and comparative examples (1) The radiative cooling-hydrogel power generation composite material prepared in Example 1 was scanned by SEM, and the results are shown in Figure 1 From the Figure 1 , the surface morphology of the upper radiative cooling layer can be observed. The radiative cooling layer prepared by electrospinning has a rich pore structure.
[0067] (2) The open-circuit voltage of the radiation cooling-hydrogel power generation composite material prepared in Example 1 was tested for a long time at the same temperature, and the hydrogel was used to generate power after being humidified. When the voltage was stable and began to show a clear downward trend, the humidification was continued for testing. The test results are shown in Figure 2 . The open-circuit voltage of a sample was repeatedly tested for a long time, and the voltage stability was good, as shown in Figure 2 .
[0068] (3) The solar spectrum absorption rate of the radiation cooling-hydrogel power generation composite materials prepared in Examples 1-3 and Comparative Example 2 was tested, and the results are shown in Figure 3 . As shown in Figure 3 , Example 1 has better low solar spectrum absorption characteristics than other samples (if the solar spectrum absorption rate is low, the solar heat intake can be reduced to provide a stable low-temperature environment for the hydrogel power generation layer).
[0069] (4) The static water contact angle of the PVDF radiation cooling layer on the upper surface of the radiation cooling-hydrogel power generation composite material prepared in Example 1 was tested, and the results are shown in Figure 4 . As shown in Figure 4 , the contact angle is greater than 90°, indicating that the PVDF radiation cooling layer has good hydrophobicity.
[0070] (5) The v-t graph of the radiation cooling-hydrogel power generation composite materials prepared in Example 1 and Comparative Example 1 was measured at the same humidity and temperature, and the results are shown in Figures 5-6 . As shown in Figures 5-6 , the radiation cooling-hydrogel power generation composite material prepared in Example 1 can maintain a stable voltage for a long time, while the voltage fluctuation in Comparative Example 1 is large.
[0071] (6) Figure 7 is the tensile property graph of the radiation cooling-hydrogel power generation composite material prepared in Example 1. As shown in Figure 7 , it has good tensile properties and a compact hydrogel structure that does not break under stress, and can meet the flexible material requirements of intelligent wearable devices.
[0072] (7) The performance of the hydrogel power generation layer in the radiation cooling-hydrogel power generation composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the performance parameters of the hydrogel power generation layer included conductivity, open-circuit voltage, porosity, and short-circuit current density. The interfacial bonding strength of the PVDF radiation cooling layer and the hydrogel power generation layer was tested, and the test results are shown in Table 1 below.
[0073] Table 1 Performance test results of the hydrogel power generation layer prepared in Examples 1-3 and Comparative Examples 1-3
[0074] As can be seen from Table 1, without adding nano-carbon black in Comparative Example 1, the conductivity of the hydrogel conductive layer is reduced from 0.1 S / m in Example 1 to 0.02 S / m, the open-circuit voltage of the moisture power generation is reduced from 0.8 V in Example 1 to 0.34 V, and the power generation stability is very poor, with a voltage fluctuation amplitude of 50% within 1 h, compared with 10% in the original scheme. It is shown that the nano-carbon black has a significant effect on the conductivity of the hydrogel, the open-circuit voltage of the moisture power generation and the power generation stability, and the performance is greatly reduced after the absence of the nano-carbon black.
[0075] In Comparative Example 2, the hydrogel power generation layer is naturally dried, and due to the uneven evaporation of water, shrinkage cracks are formed, the porosity is reduced to less than 50% of that in Example 1, the short-circuit current density of the moisture power generation is reduced by 35%, the interlayer stress is generated due to the drying shrinkage, the bonding strength is reduced by 50%, and in a humid environment, the hydrogel is prone to delamination due to swelling. It is shown that natural drying can reduce the porosity of the hydrogel and the interlayer bonding strength, and thus the moisture power generation performance and structural stability are poor.
[0076] In Comparative Example 3, the chitosan is replaced by polyvinyl alcohol, and the interfacial bonding force is reduced by more than 60% compared with Example 1; the charge transfer between the hydrogel power generation layer and the PVDF radiation cooling layer is blocked, and the short-circuit current density of the moisture power generation is reduced to about 30% of the original scheme.
[0077] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and embodiments having the same technical idea and playing the same role and effect within the scope of the technical solutions of the present application are all included in the technical scope of the present application. In addition, within the scope of the main idea of the present application, various modifications that can be thought of by those skilled in the art, and other ways constructed by combining part of the components in the embodiments are also included in the scope of the present application.
Claims
1. A radiation-cooled hydrogel power generation composite material, characterized in that, It includes a radiation cooling layer and a hydrogel power generation layer. The radiation cooling layer includes a PVDF / PPy porous membrane with a PPy coating on its surface. The hydrogel power generation layer includes chitosan / acrylic hydrogel, lithium chloride, and nano carbon black.
2. A method for preparing the radiation-cooled hydrogel power generation composite material as described in claim 1, characterized in that, Includes the following steps: S1. PVDF, methylpyrrolidone, PPy, polyvinylpyrrolidone and TiO2 are added to dimethylformamide and stirred to dissolve, and a dispersion is obtained. The dispersion is used as raw material for electrospinning to obtain a PVDF / PPy porous membrane. S2. Disperse PPy in DMF to obtain PPy dispersion, immerse the PVDF / PPy porous membrane in PPy dispersion, sonicate, and dry to obtain a radiation cooling layer. S3. Disperse acrylic acid, chitosan, lithium chloride and nano carbon black in deionized water to obtain a mixed solution; S4. Add initiator and crosslinking agent to the mixture, stir and react to obtain hydrogel power generation layer; S5. Cover the surface of the hydrogel power generation layer with the radiation cooling layer, freeze for 4-6 hours, and then vacuum dry to obtain the radiation cooling-hydrogel power generation composite material.
3. The preparation method of the radiation-cooled-hydrogel power generation composite material according to claim 2, characterized in that, The preparation method of PPy includes the following steps: S11. Disperse pyrrole, surfactant, and p-toluenesulfonic acid in deionized water to obtain a mixture; S12. Add ferric chloride aqueous solution dropwise to the mixture at 5~7℃, stir and react for 1~2 hours. After the reaction is completed, centrifuge, wash and dry to obtain PPy.
4. The preparation method of the radiation-cooled-hydrogel power generation composite material according to claim 3, characterized in that, The surfactant mentioned in step S11 includes at least one of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and sodium dodecylbenzenesulfonate.
5. The preparation method of the radiation-cooled-hydrogel power generation composite material according to claim 2, characterized in that, In step S1, the mass concentration of PVDF in the dispersion is 10%~15%, and the mass concentration of PPy is 5%~10%.
6. The preparation method of the radiation-cooled-hydrogel power generation composite material according to claim 2, characterized in that, The electrospinning parameters in step S1 are set as follows: spinning voltage 18kV, receiving voltage 6kV, feed speed 0.13mm / min, receiving distance 15cm, and spinning under the conditions of ambient temperature 25±2℃ and relative humidity 40±5%.
7. The preparation method of the radiation-cooled-hydrogel power generation composite material according to claim 2, characterized in that, The porosity of the radiation cooling layer in step S2 is 70%~90%, and the emissivity in the mid-infrared band of 8~13μm is ≥0.
9.
8. The preparation method of the radiation-cooled-hydrogel power generation composite material according to claim 2, characterized in that, Glycerin is also added to the mixture described in step S3.
9. The preparation method of the radiation-cooled-hydrogel power generation composite material according to claim 2, characterized in that, In the mixture described in step S3, the mass fraction of nano-carbon black is 0.5%~5%, and the mass ratio of lithium chloride to chitosan is 1:(2~5). The initiator in step S4 is selected from ammonium persulfate, and the crosslinking agent is selected from N,N'-methylenebisacrylamide.
10. The application of the radiation cooling-hydrogel power generation composite material as described in claim 1 in self-powered cooling systems, energy-saving building coatings, or portable cold chain packaging.